Textural Properties and Surface Chemistry of Rice Husk–Derived Biochar and Bio-silica Supports in Ni-Catalyzed Oleic Acid Deoxygenation - Wilson Leonidas Mahene; Revocatus Lazaro Machunda; Tom A. Buckman; Ali Azeko Salifu; Thomas Kivevele (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
Rice husk (RH), an abundant agricultural residue, is a promising precursor for the production of carbon- and silica-based catalyst supports for upgrading lipid feedstocks. Previous studies have shown that RH-derived biochar and biosilica can serve as effective catalyst supports in reactions involving relatively small molecules; however, their application in the deoxygenation of lipid-derived molecules remains largely unexplored. In this study, RH was converted into three distinct supports, desilicated biochar (RH-C), KOH-activated desilicated biochar (RH-AC), and biosilica (RH-SiO₂), which were systematically compared as supports for Ni catalysts in the solvent-free deoxygenation of oleic acid. The supports and catalysts were characterized by BET, TEM, XRD, XPS, and TGA. Ni/RH-AC exhibited the highest surface area (809.8 m2 g-1) but lower mesopore volume than Ni-RH-C, while Ni/RH-SiO2 showed moderate surface area and minimal microporosity. XPS revealed minimal electronic perturbation of Ni supported on biochar, whereas biosilica induced electron withdrawal. All catalysts predominantly followed the decarboxylation/decarbonylation (deCOx) pathway, although Ni/RH-SiO2 also exhibited noticeable hydrodeoxygenation (HDO). Ni/RH-C achieved the highest conversion (96%), while Ni/RH-AC and Ni/RH-SiO2 achieved 76% and 72%, respectively. TGA/DSC analysis showed greater carbonaceous material deposition on Ni/RH-AC than on Ni/RH-C, with Ni/RH-SiO2 exhibiting the lowest coking. These findings reveal a clear structure-property-performance relationship, revealing that desilicated rice-husk biochar provides higher catalytic activity, whereas biosilica offers greater stability and lower susceptibility to coking. Moreover, excessive chemical activation after desilication appears unnecessary and may even be detrimental.